Avaliação de recursos hídricos através de modelação hidrológica: aplicação do programa VISUAL BALAN v2.0 a uma bacia hidrográfica na Serra da Estrela (Centro de Portugal) - Espinha Marques, Jorge (2018)
Numerical models are needed to evaluate complex hydrological systems. VISUAL BALAN v2.0 is a lumped hydrological code which performs daily water balances in the soil, the unsaturated zone and the aquifer requiring a small number of parameters. VISUAL BALAN has been used to model the river Zêzere catchment upstream of Manteigas (Serra da Estrela, Central Portugal), in order to assess its water resources. Modelling started with the definition of sub-basins based on hydrogeomorphological units. Then, daily temperature and precipitation data from Manteigas meteorological station were extrapolated to each sub-basin considering vertical gradients. Finally, modelling with VISUAL BALAN was performed in four stages: (i) physical characterisation of each sub-basin; (ii) preliminary calculations of the daily water balance; (iii) model calibration by means of flow measurements in the river Zêzere; (iv) result analysis. This basin exhibits complex patterns in hydrometeorological variables such as rainfall and temperature. Several sub-basins have been defined in order to account for the spatial variability in hydrometeorological and geomorphological variables. The model reproduces observed flowrates while its results are coherent with the conclusions of previous studies in similar basins.